Virtual Screening of Natural Compounds as Potential SARS-CoV-2 Main Protease Inhibitors: A Molecular Docking and Molecular Dynamics Simulation Guided Approach - Deepak K. Lokwani; Sangita R. Chavan; Aniket P. Sarkate; Prabhu M. Natarajan; Vidhya R. Umapathy; Shirish P. Jain (Chemistry Proceedings)
The 2019 coronavirus (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has significantly impacted human lives, overburdened the healthcare system, and weakened global economies. The lack of specific drugs against SARS-CoV-2 is a significant hurdle toward the successful treatment of COVID-19. The SARS-CoV-2 Main protease (Mpro) is considered an appealing target because of its role in replication in host cells. Plant-derived natural compounds are being largely tested for their efficacy against COVID-19 targets to combat SARS-CoV-2 infection. To discover hit compounds that can be used alone or in combination with repositioned drugs, we curated a set of 224,205 natural product structures from the ZINC database and virtually screened it against COVID-19 Mpro. Sequential docking protocols involving different levels of exhaustiveness were performed to screen a library of natural compounds. The final 88 compounds were selected and post-processed using the MM-GBSA analysis for the generation of binding free energies. The top four compounds (ZINC000085626103, ZINC000085569275, ZINC000085625768, and ZINC000085488571) showed higher affinity against the COVID-19 Mpro enzyme selected for MD simulation studies. The RMSD, RMSF, and RoG analysis of all four compound–protein complexes indicated absolute stability during a 100 ns MD run. Furthermore, the post-MD simulation binding free energies were calculated for all four compounds and were found to be in the range of −38.29 to −18.07 kcal/mol. The in silico virtual screening results suggested that the selected natural compounds have the potential to be developed as a COVID-19 Mpro inhibitor and can be explored further for experimental research to evaluate the in vitro and in vivo efficacy of these compounds for the treatment of COVID-19.